Effect of iron therapy on fatigue symptoms in non-anaemic iron deficient women of reproductive age - Nayyer Sultana; Fariha Aslam Bajwa; Mirza Zeeshan Sikandar; Muhammad Mahtab Haider; Tayyaba Majeed (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the effect of iron therapy on fatigue symptoms in non-anaemic iron-deficient women of reproductive age. Method: The double-blind placebo-controlled randomised trial was conducted at the department of Obstetrics & Gynaecology Central Park Teaching Hospital, Lahore from March 2023 to February 2024 and comprised women aged 18-45 years who were non-anaemic, had haemoglobin level >11g/dl a fatigue score of at least 36, and a low serum ferritin level. Socio-demographic data was recorded. The subjects were randomised into Group 1 receiving iron therapy and group 2 receiving placebo. After 2 months of intervention, the fatigue scores, haemoglobin and serum ferritin levels were assessed again, and compared with baseline values. Data was analysed using SPSS 26. Results: Of the 164 subjects, 86(52.4%) were in Group 1 with mean age 30.70+18.123 years, and 78(47.6%) were in Group 2 with mean age 29.46+7.99 years (p=0.325). In Group 1, significant decrease in fatigue score and significant increase in ferritin and haemoglobin levels were noted post-intervention (p=0.05). Conclusion: Iron supplementation alleviated fatigue and enhanced serum ferritin concentration in non-anaemic, iron-deficient women of childbearing age. Key Words: Fatigue, Iron deficiency, Reproductive age, Haemoglobin, Iron therapy.